Fenomena Insecurity di Kalangan Remaja dan Hubungannya dengan Pemahaman Aqidah Islam - Qatrunnada, Jihan Insyirah; Firdaus, Salma; Karnila, Sofika Dwi; Romli, Usup (IQ (Ilmu Al-qur'an): Jurnal Pendidikan Islam, 2022)
The research aims to know the level of islamic aqidah understanding in youth, to know the level of insecurity in youth, and to test whether there is a relationship between the understanding of aqidah Islam (x) and insecurity in youth. The hypotheses put to this research are a significant influence between the understanding of aqidah Islam and the insecurity in youth. The study USES an associative descriptive descriptive method of research. Participants in the study were 96 of the 12-year-old youth. The data collection USES a questionnaire that USES the likert model's attitude scales, and is of a scale that measures islamic aqidah's understanding and insecurity. The data obtained is then decrypted, also using a Pearson product moment correlation analysis. The results are known that the level of understanding of adolescent aqidah in is very good, while the youth's insecurity level is on a good level. Then, on the correlation test obtained value are = 0.028 (p = 0.05), so the correlation between the two significant variables. The findings suggest that aqidah's understanding plays a significant role in the feelings of adolescent insecurity. Aqidah's understanding is viewed as an important aspect that influences youths in the face of difficult transition times.